Intention To Purchase Halal Medicine: The Mediation Effect of Halal Certificates - Alfajriyani, Siti; Ashari, Nesha Rizky; Amalikhah, Novita Ayu; Azhar, Jeihan Ali (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: This research aim for now intention generation Z in inner DKI Jakarta buy halal medicines with use theory action planning (TPB) through attitudes, norms subjective and control perceived behavior, with halal certificate as variable mediation.Design/Method/Approach: This research use approach quantitative with primary data. Data collection techniques use questionnaires / questionnaires distributed online via Google from, and data analysis using SEM.Findings: Research result This show that attitudes, norms subjective and control behavior influential positive and significant to intention buy halal medicines. However, attitudes, norms subjective and controlled perceived behavior No influential in a way positive and significant to intention buy halal medicines with halal certificate as variable mediation. Apart from that, there is no halal certificate either influential to intention buy halal medicines. So that whether there is or not halal certificate in A drug No will influence intention somebody in buy halal medicines.Originality/Values: Contribution in study This is for see is intention buy halal medicines with halal certificate as variable mediation can influence intention generation Z in inner DKI Jakarta buy halal medicines